Perancangan Sistem Informasi Inventory pada PT. Alssa Corporindo Menggunakan Metode Pengembangan Sistem Waterfall - Rahmatika Rahmatika (Jurnal Informatika Universitas Pamulang, 2021)
PT. Alssa Corporindo is a company engaged in the distribution of electronics and telecommunications. PT. Alssa Corporindo at all times supervises the recording of inventory. Inventory data processing is usually recorded in the general ledger based on the receipt of the purchase of goods from the supplier of goods. Recording is done so that the transaction of goods entering and leaving the warehouse can be known. So far, the recording of these transactions is done using paper media as transaction reports made by the warehouse department. Then the office administration section re-records these reports into the general ledger. The process of recording these transactions creates problems because errors often occur in recording or the information cannot be accessed quickly. Making reports of goods entering and leaving the warehouse is experiencing difficulties because there are more and more proof of receipts for each transaction. As a result of the inaccurate reporting data, the stock of goods is not in accordance with consumer demand. Searching for data on goods in the warehouse is very difficult because the documents between goods and physical goods are irregular. Based on these problems, research was conducted to overcome these problems. The research was conducted in system development using the WaterFall method. This research succeeded in building a new system to process inventory at PT. Alsa Corporindo.